Effect of acute working memory stimulation on motor learning. - MACEDO, LILIAN C.; BATISTA, MARCO T. S.; GONÇALVES, VIVIANE L.; LAGE, GUILHERME M. (Brazilian Journal of Motor Behavior, 2025)
BACKGROUND: Working memory (WM) plays an important role in motor learning, particularly at the beginning of the process. AIM: The present study aimed to investigate the effect of acute working memory stimulation on the learning of a complex motor skill. METHODS: Twenty-four college students (12 males, 12 females), aged 18 to 40 years, practiced the golf putting motor task. Twelve participants in the experimental group performed the N-back cognitive task (level two-back) for five minutes as acute WM stimulation before the golf putting motor task, while the control group remained seated looking at a blank screen for the same duration. RESULTS: The results found that learning occurred in both groups; however, acute WM stimulation did not enhance this learning process in the stimulated group. Unexpectedly, WM stimulation caused an initial impairment in performance for the stimulated group during the first acquisition block. INTERPRETATION: This suggests that acute WM stimulation, as applied in this study, did not facilitate learning and may have temporarily hindered initial performance in a complex motor skill.